The Role of Integrated Marketing Communications in Promoting Algerian Sports Tourism in Light of Social Media Platforms - Zahra Kemel; Hanane Chetibi (İşletme Bilimi Dergisi)
This study seeks to explore the link between integrated marketing and the growth of sport tourism in Algeria, emphasizing the role social media in shaping Algeria sport tourism indentity. To achieve the objectives of the study, the researchers used the descriptive and analytical approach due to its relevance to this type of research. The sample was an intentional random sample of people working in the Sports Directorate and tourism and travel institutions in Algeria. 80 questionnaires were distributed, and the research included two main variables, the independent variable represented by integrated marketing communications. In light of social media platforms and the dependent variable is sports tourism, the study reached results including that integrated marketing communications via social media platforms have a role in promoting sports tourism in Algeria, and that the obstacles facing the use of integrated marketing communications via social media platforms have a role in hindering the promotion and revitalization Sports tourism in Algeria, and in light of the results, recommendations were presented.